Preformulation Study of Buccoadhesive Monolayered Tablets of Carvedilol - S.VIJAYA KUMAR,; B.STEPHEN RATHINARAJ,; GANESH SHESHRAO BANGALE, (International Journal of Pharma and Bio Sciences, 2010)
The purpose of this research work was to establish mucoadhesive buccal tablets of carvedilol in the forms of monolayered tablets. The tablets were prepared using Sodium methyl cellulose (NaMC ) , sodium alginate and Methocel K15M as bioadhesive polymers to impart mucoadhesion. Buccal tablets were evaluated by different parameters such as weight uniformity, content uniformity, thickness, hardness, surface pH, swelling index, ex vivo mucoadhesive strength, In-vitro drug release, and In- vitro drug permeation. The present study concludes that mucoadhesive buccal tablets of carvedilol can be a good way to bypass the extensive hepatic first-pass metabolism and to improve the bio availability of carvedilol.